ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DENGAN MENGGUNAKAN MODEL PROJECT BASED LEARNING PADA MATERI FPB DAN KPK - Siti Maysarah (AXIOM : Jurnal Pendidikan dan Matematika, 2018)
Creative thinking is required by the students as future supplies.However, the reality is very few teachers found creativemathematics, thus making the students find it difficult to applymathematics in everyday life. One model of learning thatencourage students to creative thinking is Project Based Learning(PjBL). Project based learning is a learning model through a set ofspecific projects. Project based learning model is a model oflearning that starts from the provision of challenging questionsabout a phenomenon, then assign students to do an activity,focusing on the collection and use of evidence, not just deliveringinformation directly and the emphasis on rote learning processesused in order to more meaningful. Based on the research results of28 students in the class V-A MIS Nurul Falaq Tanjung Morawa onthe application FPB and KPK by analyzing indicators of creativethinking abilities are problem sensitivity, fluency, flexibility,originality, and elaboration. The average of prolem sensitivityindicator is 4,0 with very exelent category. The average of fluencyindicator is 3,8 with exelent category. The average of flexibilityindicator is 4,0 with very exelent category. The average oforiginality indicator is 2,0 with dissapointed category. The averageof elaboration indicator is 4,0 with category very excellent. It canbe concluded that: the model of project-based learning can be usedas a learning model to analiyzed mathematical creative thinkingabilities of students.